Relevansi Ranah Kognitif dan Motivasi Berprestasi dengan Hasil Belajar PAI - Nurjannah, Nurjannah (JOEAI (Journal of Education and Instruction), 2019)
The purpose of this study was to determine the relationship between cognitive style and achievement motivation style with the learning outcomes of Islamic Religious Education (PAI) students of SMP 5 Rejang Lebong. The research method uses survey methods with a correlational engineering approach. The research data were sourced from cognitive style test results and achievement motivation tests and PAI learning outcomes obtained from report cards. The results showed there was no significant relationship between cognitive style with PAI learning outcomes with Ï-value 0.122. There is a significant relationship between achievement motivation and PAI learning outcomes with Ï-value 0.022. Cognitive style and achievement motivation are related to PAI learning outcomes Ï value = 0.031> 0.05. Conclusion, there is no significant relationship between cognitive style with PAI learning outcomes. There is a significant relationship between achievement motivation and PAI learning outcomes. Cognitive style and achievement motivation are jointly related to the learning outcomes of PAI students of Rejang Lebong Middle School. Keywords: Achievement, PAI Learning Outcomes, Cognitive, Motivation